Agriculture, natural resources, environment and sustainable development in Costa Rica. - Morera, Jorge A. (Agronomía Mesoamericana, 2006)
The sustainable agriculture in Costa Rica must recognize the need of intensifying the productivity as a way to support the increasing demand created by the population growth, but at the same time it has to prevent the best use and conservation of the natural resources. Without natural resources there is no agriculture and without it there isn’t food support. It’s hoped that Costa Rica can satisfy the growing demand of food and other agriculture products; avoiding the fast process of degradation that our soils and forest are suffering. The sustainable agriculture process in Costa Rica and other countries of the region presents an increasing demand of land and natural resources; which causes social, economic and ecological conflicts and competence. This is why Costa Rica must organize a strategy of sustainable development that contemplates the effects of the demographic growth, food support, biodiversity protection, ecosystem regeneration, development of friendly technologies with the environment, regulation on the use of natural resources and the formation of better thought human beings.